A atitude do consumidor no processo de compra de refrigerantes: um estudo da influência das marcas regionais - Sala, Daniela Georgina Somaio Teixeira (2011)
The study presents a research about the attitude of the consumer in the buying process of regional brands of soft drinks, also known as brand B. An overview of the soft drinks market in Brazil is drawn, measuring size, characteristics, trends, strategies and players in this sector. A survey from secondary sources, has the leading brands and regional operating in this market, as well as their respective operational strategies. It also presents the profile and aspirations of consumers with low income, primary target audience of regional brands. Completing the study, a quantitative field research is applied to a sample of 290 consumers in the city of Araçatuba, located in São Paulo. We investigated factors influencing the decision to buy soft drinks, attributes relevant to the choice of soft drink brands, the brands acquired in this region, frequency and locations to purchase, beyond the mechanisms re-branding